School/University Partnerships - A Time to Disenthrall Ourselves - Stuart B. Ervay; Daniel Lumley (Educational Considerations, 1988)
It is essential that strong and on-going linkages exist between those who prepare teachers and the field-based practitioners who are intimately acquainted with student needs.